Urbanisation and land use transition in a second-tier city: The emergence of small factories in Gimpo, South Korea. (September 2018) - Shin, HaeRan; Chae, Sangwon
Abstract: This research incorporates tenets of growth regime theory through the case of Gimpo, a Seoul-dependent second-tier city. To put second-tier cities in a context that includes the concept of Korean and East Asian nuances, we suggest conceptualising the development of a growth regime theory through a dialogue that considers the departure from an agreement with the Western paradigm and path dependence of developmental states. The development of Gimpo has been heavily constrained by the central government's control of the overwhelming growth of the Seoul Capital Area. Since the 1990s, however, the deregulation of the area has driven the creation of thousands of small factories. Based on in-depth interviews, a focus group, archives, and site visits, the research demonstrates, first, that the central government and the city government have wavered between remaining interventionist and taking a neoliberal approach. The state allowed industrialisation of Seoul's suburban cities, and the city government attempted to attract businesses into planned industrial parks but ended up allowing even more dispersed small factories. Second, the growth regime has emerged, including city government, real estate agencies, village leaders, landowners, entrepreneurs, and migrant-supporting organisations. They drove the development of the small factories by responding to policies and the influx of migrant workers. The village leaders, eejangs, who are both elected leaders and landowners, played a critical role by turning into developers and entrepreneurial mediators and persuading landowners to accommodate factories on their agricultural land. By examining the interaction between the urban growth regime and urban hierarchy, this research contributes to the debate on urban growth and development in various contexts.